Continuous Long-Term Entecavir Therapy in Na?ve Chronic Hepatitis B Patients Showing Partial Virologic Response (Gut and Liver, 2013)
Background/AimsWe investigated the efficacy of continuous long-term entecavir 0.5 mg treatment in na?ve chronic hepatitis B patients showing a partial virologic response (PVR).Methods : A total of 227 patients were included. PVR was defined as a more than 1 log10 IU/mL decline in detectable serum hepatitis B virus (HBV) DNA by polymerase chain reaction (PCR; ≥20 IU/mL) at week 48. A complete virologic response (CVR) was defined as undetectable serum HBV DNA by PCR (<20 IU/mL) at week 48.Results : At week 48, the rate of the PVR was 64/227 (28.2%). Among patients with PVR, the cumulative rates of virologic response (serum HBV DNA <20 IU/mL) at weeks 96 and 144 were 45.2% and 73.8%, respectively. The cumulative rates of genotypic resistance were not significantly different between patients with a PVR and patients with a CVR (p=0.057). However, the cumulative rates of virologic breakthrough were higher in patients with PVR than in patients with CVR (4% vs 0% and 11.2% vs 0% at weeks 96 and 144, respectively; p<0.001).Conclusion : sLong-term continuous entecavir 0.5 mg treatment in patients with a PVR resulted in an additional virologic response without a significant increase in genotypic resistance. However, the rate of virologic breakthrough was higher in the partial responders.